2003
DOI: 10.1002/jmri.10295
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐center 1H MRS study of the AIDS dementia complex: Validation and preliminary analysis

Abstract: and the HIV MRS Consortium † Purpose: To demonstrate the technical feasibility and reliability of a multi-center study characterizing regional levels of the brain metabolite ratios choline (Cho)/creatine (Cr) and myoinositol (MI)/Cr, markers of glial cell activity, and N-acetyl aspartate (NAA)/Cr, a marker of mature neurons, in subjects with AIDS dementia complex (ADC). Materials and Methods:Using an automated protocol (GE PROBE-P), short echo time spectra (TE ϭ 35 msec) were obtained at eight sites from unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 39 publications
5
76
0
Order By: Relevance
“…The imaging study protocol was directed and monitored by the central site (MGH). Initial MRS studies conducted by the consortium revealed high consistency of MRS spectra across the different imaging sites (Lee et al, 2003). T1-weighted sagittal and high-resolution proton-density images were analyzed in this study.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging study protocol was directed and monitored by the central site (MGH). Initial MRS studies conducted by the consortium revealed high consistency of MRS spectra across the different imaging sites (Lee et al, 2003). T1-weighted sagittal and high-resolution proton-density images were analyzed in this study.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…As described in detail previously (Lee et al, 2003), spectra data were sampled in the basal ganglia with the voxel placed in the putamen. Voxel placement verification was determined at the central processing site.…”
Section: Mrsmentioning
confidence: 99%
“…The specifics of this study have been presented in more detail elsewhere (Lee et al 2003;Chang et al 2004). Briefly, data were collected at 11 participating imaging centers: Massachusetts General Hospital (MGH, the central site), University of California Los Angeles, Harbor-UCLA Medical Center, University of Pennsylvania, University of Washington, University of Rochester, Mt.…”
Section: Study Subjects and Imaging Protocolsmentioning
confidence: 99%
“…MRS parameters included TE=35ms, TR=3000ms, voxel size=6cm 3 (20×20×15mm 3 ), 128 acquisitions, spectral width=2500Hz, and 2k data points. For consistency, the sequence was compiled and distributed to participating sites by the MGH-NMR Center (Lee et al 2003). Spectra were localized to three brain regions corresponding to different tissue types: midline posterior parietal cortex (gray matter), mid-frontal centrum semiovale (white matter) and basal ganglia (deep gray matter).…”
Section: Study Subjects and Imaging Protocolsmentioning
confidence: 99%
See 1 more Smart Citation